The Arkansas Crisis Stabilization Study: Health Service Utilization and Jail Booking Outcomes of a Longitudinal Cohort - McLaughlan, Cassandra L. (Criminal justice and behavior, 2025)
Crisis stabilization units (CSUs) provide short-term residential mental health and substance use treatment to people experiencing acute behavioral health crises. While preliminary evidence suggests CSUs may reduce justice-involvement and increase connection to outpatient health services, nuanced longitudinal studies are lacking. In this study, 208 CSU patients completed assessments during admission and at 1 month, 3 months, 6 months, and 12 months thereafter. Jail booking data for CSU catchment areas was also collected and linked to participant records. Compared with their recent service use at baseline, participants were more likely to use outpatient medical care and less likely to visit emergency departments or use inpatient psychiatric/psychological services after their CSU stay. Jail bookings did not change significantly following CSU admission. Taken together, CSUs appear to play a key role in the health care continuum, providing a short-term window of opportunity wherein other interventions could be integrated to promote longer-term improvement; recommendations and future directions are discussed.